A prospective study investigating gross motor function of children with cerebral palsy and GMFCS level II after long-term Botulinum toxin type A use - Jane Valentine; Sue-Anne Davidson; Natasha Bear; Eve Blair; Lisa Paterson; Roslyn Ward; David Forbes; Catherine Elliott (BMC, 2020)
Abstract Background The aim of this study is to contribute to the knowledge base on the long-term outcomes of evidence-based medical interventions used to improve gross motor function in children and adolescents with Cerebral Palsy. Method Prospective cohort study of children with Cerebral Palsy in the birth years 2000-2009 attending a tertiary level service for children with Cerebral Palsy who's first recorded Gross Motor Function Classification System level was II. Results A total of 40 children were eligible for the study, of whom 28 (72.7%) enrolled. The Botulinum toxin A treatment for this cohort, (median and interquartile ranges) were: total number of lower limb Botulinum toxin A injections 11 (6.7, 5.5); total dose of Botulinum Toxin A per lower limb treatment 6.95 u/kg (4.5, 11); and dose of Botulinum Toxin u/kg/muscle 2.95 (2.2, 4). For all 28 subjects there was a median of 15 (8.5 to 22) Gross Motor Function Classification System level recordings: six of the 28 children (21.4%) improved from level II to level I, the remaining 22 children remained stable at level II (78.6%). In this highly treated population, the average 66 item Gross Motor Function Measure score for the 22 children in level II was 72.55, which is consistent with the mean of 68.5 reported in the original Ontario cohort. Conclusion This cohort study has confirmed that children with Cerebral Palsy, Gross Motor Function level II treated at a young age with repeated doses of Botulinum Toxin A within an integrated comprehensive service, maintain or improve their functional motor level at a later age.